Effects of the Boron-Doped p+ Emitter on the Efficiency of the n-Type Silicon Solar Cell - Eun-Young Kim; Jeong Kim (Advances in Materials Science and Engineering)
The optimum structure of the p+ emitter for the n-type silicon solar cell was determined with the simulation of the boron doping concentration. The boron concentration (NB) in the p+ emitter was varied in the range of 1×1017 and 2×1022 atoms/cm3 while maintaining the base doping concentration at 2×1016 atoms/cm3. With the increase of the boron concentration, the open circuit voltage (VOC) of the cell increased up to 0.525 V and then was nearly saturated at NB>5×1018 atoms/cm3. On the other hand, the short circuit current density (JSC) began to decrease at NB>1×1019 atoms/cm3 due to the increase of the surface recombination loss, and without considering the variation of the contact resistance along the emitter doping level, the maximum efficiency of the cell was obtained at around NB=5×1018 atoms/cm3. While the contact resistance of the electrode decreases with the increase of the doping concentration in the p+ emitter, and with consideration of the variation of the contact resistance, the optimum value of NB for maximum efficiency shifted to the higher doping level.